2012
DOI: 10.1007/s13224-012-0206-0
|View full text |Cite
|
Sign up to set email alerts
|

GnRH Agonists: Do They Have a Place in the Modern Management of Fibroid Disease?

Abstract: In the management of women with fibroid disease, GnRH agonists (GnRHa) are frequently used to reduce volume and vascularity before myomectomy, apparently to render the operation easier and reduce operative blood loss, and to enable a transverse supra-pubic incision instead of a midline vertical one. They induce amenorrhoea and thus aid in the correction of pre-operative anaemia. Other gynaecologists use GnRHa to shrink sub mucous fibroids greater than 5 cm in diameter to facilitate access and reduce blood loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Therefore, our analysis fails to confirm the theoretical beneficial effects (more receptive endometrium, resting ovaries) of waiting ≥ one cycle. Indeed, it could be speculated that there could be a rebound effect similar to that described in the ovary 62,63 or with the growth of myomas after stopping medical GnRH analog treatment 64 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our analysis fails to confirm the theoretical beneficial effects (more receptive endometrium, resting ovaries) of waiting ≥ one cycle. Indeed, it could be speculated that there could be a rebound effect similar to that described in the ovary 62,63 or with the growth of myomas after stopping medical GnRH analog treatment 64 …”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane review on the preoperative use of GnRH comments that “fibroid capsule will become less evident and may be missed, tumours will not “shell out” cleanly and the excision may be more difficult” [ 22 ]. The literature also reports that the use of GnRHa is not cost-effective [ 23 ], delays surgery, and is associated with significant side effects and bone demineralization, and there are much cheaper alternatives such as progestogens to prevent menstruation while correcting anemia [ 24 ]. Further evidence is emerging regarding the preoperative use of UPA which could be a better alternative to GnRH: a recent study from Canada investigated the surgical experience of patients that underwent laparoscopic or robotic myomectomy following UPA treatment and found no difference compared to non-treated patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… 46 Furthermore, although the data are limited and based mainly on surgical experience, many surgeons avoid the pre-operative use of GnRH analogues as there are concerns that they may distort the fibroid capsule with a resultant loss of surgical planes between the fibroid and myometrium potentially making the surgery more difficult and time-consuming. 47 In a randomised study comparing premenopausal women with or without pre-operative use of GnRH analogues, Campo and Garcea 48 found that laparoscopic myomectomy took longer in women with pre-operative treatment and they concluded that the use of GnRH analogues did not offer any advantages. In a more recent systematic review and meta-analysis, Chen et al 49 concluded that there was no difference in operating times or blood loss with or without pre-operative treatment.…”
Section: Modern Management Of Fibroidsmentioning
confidence: 99%